Cyclization of ortho-ethynylbiaryls as an emerging versatile tool for the construction of polycyclic arenes. (June 2019) - Pankova, Alena S.; Shestakov, Aleksandr N.; Kuznetsov, Mikhail A.
Abstract : Cyclization and cycloisomerization of ortho -aryl(ethynyl)arenes provide an easy direct access to fused polycyclic aromatic carbo- and heterocycles. This methodology has demonstrated an impressive progress in the recent years. The goal of this review is to give a comprehensive outlook on the synthetic potential, scope, limitations, and mechanistic aspects of the cyclization reactions. The material is arranged according to the activation method that can be used to induce cyclization: pyrolysis, metal catalysis, electrophilic activation, radical induction, base catalysis. Particular attention is paid to the specificity of ortho -ethynylbiaryls with a heterocyclic central core. The bibliography includes 257 references.